Development Of Arabic Gramatica Book With The Concept Map Of Tony Buzan Model/ تطوير كتاب متممة الآجرومية باستخدام خريطة المفاهيم على نموذج توني بوزان - Ahmad Jaunanto; Imam Asrori; Moh Khasairi (Ijaz Arabi Journal of Arabic Learning, 2022)
Nahwu or Arabic gramatica is difficult for students. This study focuses on the Mutammam al-Ajrūmiyyah, an Arabic grammatical book popular in Indonesia. This study aims for three purposes: the development of the Mutammimah Al-Ajramiyah book using the Tony Buzan model, concept map, and describing the results of expert validation of the validity of the Mutammimah Al-Ajurumiyah book using the Tony Buzan concept map model, and knowing the effectiveness of using the Mutammimah Al-Ajurumiyah book using the Tony Buzan model concept map. The researcher used the Borg and Gall development approach, which was summarized into data analysis, information gathering, planning, development, expert validation, revision, field experiment, and final product. The samples in this study were fourth-grade students of the Anwar Huda Islamic boarding school in Malang, Indonesia and nahwu teachers in that class. The data in this study consisted of two types: quantitative data and qualitative data, and the methods of collection were interviews, observations, questionnaires, and exam tests. The results of this development are (1) the Mutamimmah al-Ajurumiyah book with a concept map of the Tony Buzan model, which consists of eight subjects, as well as Indonesian translations, tables, and practice questions, (2) the results of the validation of subject matter experts get 87%. Concept map experts obtained 64%. and the results of the media expert validation got 66%, (3) the Paired samples test results obtained a significant value of p = 0.000 0.05, which indicates that there is a significant difference between the pre-test and post-test scores on the test scores, meaning that the student's test scores increased significantly after using the developed book.